2006
DOI: 10.1139/g06-094
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analyses of the wheat genomes based on expressed sequence tags (ESTs) related to abiotic stresses

Abstract: To gain insights into the structure and function of the wheat (Triticum aestivum L.) genomes, we identified 278 ESTs related to abiotic stress (cold, heat, drought, salinity, and aluminum) from 7671 ESTs previously mapped to wheat chromosomes. Of the 278 abiotic stress related ESTs, 259 (811 loci) were assigned to chromosome deletion bins and analyzed for their distribution pattern among the 7 homoeologous chromosome groups. Distribution of abiotic stress related EST loci were not uniform throughout the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 88 publications
0
7
2
Order By: Relevance
“…While QTL number varied between the three hexaploid wheat genomes, it was not significantly different from what would be predicted on the basis of physical size (Gill et al, 1991), suggesting that the contribution of the three genomes to stress tolerance may be similar. This finding is in contrast to Ramalingam et al (2006), who reported a higher gene density of stress‐related expressed sequence tags (ESTs) mapping to the D genome and to reports of Aegilops tauschii , the D genome progenitor of common wheat, being a rich source of stress‐tolerance alleles in synthetic hexaploids (Trethowan and Mujeeb‐Kazi, 2008). The largest number of individual QTL were located on the Group 2 chromosomes (163 QTL), consistent with the physical bin‐mapping of 142 abiotic stress‐related EST loci to the Group 2 chromosomes, the most of any chromosome group (Ramalingam et al, 2006).…”
Section: Discussioncontrasting
confidence: 74%
“…While QTL number varied between the three hexaploid wheat genomes, it was not significantly different from what would be predicted on the basis of physical size (Gill et al, 1991), suggesting that the contribution of the three genomes to stress tolerance may be similar. This finding is in contrast to Ramalingam et al (2006), who reported a higher gene density of stress‐related expressed sequence tags (ESTs) mapping to the D genome and to reports of Aegilops tauschii , the D genome progenitor of common wheat, being a rich source of stress‐tolerance alleles in synthetic hexaploids (Trethowan and Mujeeb‐Kazi, 2008). The largest number of individual QTL were located on the Group 2 chromosomes (163 QTL), consistent with the physical bin‐mapping of 142 abiotic stress‐related EST loci to the Group 2 chromosomes, the most of any chromosome group (Ramalingam et al, 2006).…”
Section: Discussioncontrasting
confidence: 74%
“…Another cis element, MYCCONSENSUSAT, found in the promoter regions, was involved in the dehydration stress response, which further supports our findings that indicated that all the 3 genes were upregulated under drought stress. ARR1AT is a binding element for the cytokinin response regulator ARR1, which is found in Arabidopsis (Ramalingam et al, 2006;Wu et al, 2007); it acts an upregulator of ATG6 genes and was observed in rice leaves treated with cytokinin, thereby indicating the involvement of ATG6 genes in the cytokinin signaling network (GEO dataset GSE6719; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The complete sequencing of the wheat genome is challenging because of its large genome size (16,000 Mb; Bennett and Leitch 2005). Nevertheless, mapping and characterizing ESTs offers a manageable approach to the complex architecture and functioning of the wheat transcriptome and helps in unravelling the genetics of stress response (Ramalingam et al 2006;Barnabas et al 2008). Through SSH libraries we have generated a collection of heat stress responsive genes critical for various growth stages in wheat.…”
Section: Discussionmentioning
confidence: 99%